A Framework for Geodesign: Changing Geography by Design - Srivanit, Manat (International Journal of Building, Urban, Interior and Landscape Technology, 2016)
Geographic Information System (GIS) technology has a long history of driving environmental understanding and decision making. Policy makers, planners, scientists, and many others worldwide rely on GIS for data management and scientific analysis. As the challenges facing our natural and human environments evolve to new levels of complexity, tools must also evolve (ESRI, 2010). The disciplines of geography and design have been around for a long time, but in the last half of the twentieth century they began co-evolving with computing technology. When a small group of people began exploring the new frontier of “computational geography” by blending maps and geographic information with mathematics and computing, they changed the way we see and understand our word. Similar developments occurred in the application of computing technology to the design of major changes to the environment. A new age of geography is dawning: the age of designing.